The allocation of Polish Rural Development Program funds. The Optimization Approach - Kiryluk-Dryjska, Ewa (Alokacja funduszy polskiego Programu Rozwoju Obszarów Wiejskich. Podejście optymalizacyjne, 2011)
Polish Rural Development Program 2007-2013 amounts to 17 billion EUR, from which over 76% is derived from the EU budget. The allocation of these funds takes place at the country level, with multiple conflicts of interest arising among the stakeholders. The pivotal problem is how the rural development budget can be best allocated in order to promote the economic growth of the agricultural sector, the sustainable development of rural areas, and the preservation of natural resources. In this paper, I apply a restricted weighted sum model to optimize the resource allocation of Rural Development Program 2007-2013. The modeled results are compared with the actual allocation performed by the Ministry of Agriculture and Rural Development in Poland
Ekonomia = Economics, 2011, Nr 2 (14), s. 151-159
Keywords: allocation; rural development; MCDA